The Role of the Principal in Increasing Teacher’s Work Motivation at Madrasah Ibtidaiyah Indralaya - Malini, Ema; Ahyani, Nur; Mahasir, Mahasir (Yayasan Sembilan Pemuda Indonesia, 2023)
This study aims to describe the role of school principals in increasing teacher motivation an overview of teacher work motivation and strategies for the role of school principals in increasing teacher motivation. The research method used is a qualitative with the research location at Madrasah Ibtidaiyah Indralaya Ogan Ilir, South Sumatra. Data collection techniques by interview observation and documentation, with data analysis techniques in the form of data redundancy, data/display presentation, and conclusions. The results obtained in this study indicate that the role of the principal as a motivator in optimizing teacher performance is good because and several indicators have been carried out a lot, while the indicators are paying attention to a neat and clean work environment, providing seminars/training meetings, discipline, encouragement of awards, and provision of learning resources or media. The teacher’s work performance is quite good, because of several indicators, namely preparing lesson plans, managing learning activities, holding interpersonal relationships, conducting assessments and mastering academic studies.